AN APPROXIMATION IN CUBAN CULTURE ABOUT THE MOLLUSKS - Armiñana-García, Rafael (2020)
An analysis of the main beliefs, myths, uses and other social and cultural manifestations of mollusks (snails, slugs and others) in Cuba is presented, based on ethnological work carried out in different locations on the island of Cuba, from the 2010, until 2020. In order to carry out the research, methods of sociocultural research, such as those at the theoretical and empirical level, were used in their dialectical interrelation, among which the following stand out: historical - logical, analytical - synthetic, inductive - deductive, all from the theoretical level, and from the empirical level, the interview and documentary analysis. More than 500 residents throughout the national territory were interviewed and the answers to the questions that the authors considered the most significant were chosen. The presence of snails at different levels of the social and cultural life of the Island of Cuba, gives mollusks an extraordinary importance. Key words: Cuba – mollusks – shells – slug – snails